Interleaved-LoRa Transmission Scheme for Satellite IoT - Jin LUO; Jiabao XIA; Yang BAI; Baoming BAI (天地一体化信息网络)
The transmission distance of satellite IoT is much further than terrestrial IoT, resulting in a signifi cant power loss on the transmission link.Thus the received signal power at a receiver will be signifi cantly lower.Combining a high-performance FEC coding and LoRa modulation with a signifi cant spreading factor enables reliable communication at very low signal-to-noise ratios.However, LoRa modulation dramatically decrease spectral effi ciency as the spreading factor increases.An interleaved LoRa transmission scheme that could achieved high spectral effi ciency with a low bit error rate (BER) was proposed.Firstly, a non-coherent soft demodulation algorithm was presented for LoRa and the corresponding performance comparison with the use of Turbo and LDPC codes.Then proposed a soft demodulation algorithm for interleaved-LoRa transmission.Simulation results showed that Turbo coded interleaved-LoRa system outperformed the uncoded system by about 4 dB at a BER=10-5, which was equivalently to a 55%~57% improvement on communication distance in free space.Furthermore, the spectral effi ciency was improved by approximately 23% compared to the existing Turbo-LoRa scheme.